2004
DOI: 10.1076/call.17.1.51.29710
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Digitized Second Language Videotext

Abstract: Despite the widespread use of digital video and, increasingly, multimedia in listening instruction throughout second language programs, little is known about how learners attend to dynamic visual elements in comprehension. A lack of research in how listeners engage with videotext retards the development of computer-based listening skills. This investigation seeks to describe what learners do when they attend to digital video media. In conjunction with Japanese language instructors, three authentic Japanese new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 23 publications
4
49
0
Order By: Relevance
“…Moreover, results confirmed that the students were confused in the third input mode, which contained aural and non-verbal input with subtitles, and they would not prefer this type especially in the first listening if they were to be exposed to the same lecture again. This finding in the present study is totally in line with the results reported by Gruba (2004). In his study, Gruba found that when the information was presented through dual modes (in news broadcasts), this type of modality hindered comprehension of upper-intermediate level foreign language learners, as in the present study, by putting a lot of strain on their limited working memory.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, results confirmed that the students were confused in the third input mode, which contained aural and non-verbal input with subtitles, and they would not prefer this type especially in the first listening if they were to be exposed to the same lecture again. This finding in the present study is totally in line with the results reported by Gruba (2004). In his study, Gruba found that when the information was presented through dual modes (in news broadcasts), this type of modality hindered comprehension of upper-intermediate level foreign language learners, as in the present study, by putting a lot of strain on their limited working memory.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, with the u‐learning support, the participants showed significant improvements in their listening comprehension, based on the quantitative data, which echoes the studies of Chang et al () and Liu and Chu (). Moreover, the use of videos also increased the students' learning motivation and improved their listening comprehension (Gruba, ). Additionally, the interviewees had positive attitudes towards the videos they made at the end of the program, as this practice helped them review what they had learned.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, such as Tuffs and Tudor (1990), Baltova (1994), and Brett (1997), lend support to this observation. Similarly, Gruba (1999; 2004) also observed that some visuals may not always be supportive, because they may add little to the development of a macrostructure of the news. Indeed, further questions remain about the transferability of such process to listening comprehension in a test‐like event which mainly activates short‐term memory to process listening input (see Vandergrift 2007).…”
Section: Related Literaturementioning
confidence: 98%
“…Allan 1985; Lonergan 1984; McGovern 1983) and morerecently have been increasingly used and discussed in the context of testing foreign language learners' listening comprehension skills (e.g. Coniam 2001; Feak and Salehzadeh 2001; Ginther 2001; 2002; Gruba 1997; 1999; 2004; Guichon and McLornan 2008; Ockey 2007; Wagner 2002; 2007; 2008). On the basis of such studies, Brindley's comment that ‘video‐mediated language testing remains relatively unexplored’ (1998: 180) is clearly less true today; however, research on using videos in language testing is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%